Organized crime in North America - Albanese, Jay (Henry Stewart Talks, 2008)
Organized crime, Definitions, types and history, The gangster era and rise of the mafia in 20th century America, Organized crime in Canada and Mexico, The ethnicity trap and models of organized crime structure, Prosecution and sentencing in organized crime cases, The future of organized crime
Archived at 2022/04/03